Aplicación Web para fomentar pensamientos matemáticos desde la geometría para estudiantes de cuarto y quinto de primaria (2021)
It begins with the formulation and description of the problem, this allows us to define the general objective and the specific objectives, the state of the art is analyzed, some applications that were considered relevant are mentioned, the impact of it and the innovation component are mentioned, all this will allow us to have a frame of reference on the approach of the project